Application Integration 360Â° Method Feedback and Analytical Hierarchy Process as a Performance Assessment of Employees - Syatoriah, Chumayrotus; Wahyani, Widhy (Inscientech: Journal of Industrial, Science and Technology, 2017)
Human Resources (HR) in a companies and industry is needed to create high competitiveness based on performance results conducted on the company and the industry. In an effort to improve the quality of human resources, a company needs to conduct performance appraisals. Therefore, the Cooperative "X" necessary to assess employee performance that is objectively by 360 degreemethod feedback and Analythical Hierarchy Method (AHP). From the research results, obtained performance variable priority is adaptability and flexibility are at the sub-variables to adjust to any changes in the work environment. The highest value for employee performance by initials IM (0.64), the worker who has has initialA (0.95), the initial U (0.37) is in the variable adaptation and flexibility. The highest value for employee performance by initial Y (0.40), the initial S (0.35) that the co-operative variables and cooperation. The highest value for employee performance with the initial E (0.61), the initial N (0.60), S (0.57), and D (0.83) is in the variable reliability / accountability. The highest value for employee performance with the initial C (0.06) is in the variable and problem-solving initiatives. The highest value for employee performance H (1.07) is in the variable quality of work. Method 360-degree performance appraisal feedback integration more effectively and objectively describe the performance of employees from several sources assessor and obtain material for evaluation as a reference in the development of quality employees.